Determinantes da taxa de poupança das famílias Brasileiras: Evidência microeconômica com as POFS 2002-2003 e 2008-2009 - Marcos Antonio Coutinho da Silveira; Ajax Reynaldo Bello Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– With data from the Household Budget Survey of 2008-2009, the study investigates the demographic and socioeconomic determinants of saving rate of Brazilian families in the recent past. The main results are consistent with the predictions of the theory of life / permanent income cycle, properly extended to incorporate institutional and structural aspects of Brazilian economic relevance such as credit restrictions, particularly for the poorest sections of the population, comprehensive public retirement schemes and government transfers. It is evident the importance of the life cycle and transitory shocks in current income in explaining fluctuations in the saving rate. Evidence for the existence of precautionary savings due are also found. Heterogeneity tests did not indicate significant differences in the effects of the explanatory variables when the sample is segmented by POF or education level.
Keywords: E21; 330; saving rate; households